Survival and disease recurrence in patients operated for small intestinal neuroendocrine tumors at a referral hospital. (December 2020) - Folkestad, Oddry; Wasmuth, Hans H.; Mjønes, Patricia; Fougner, Reidun; Hauso, Øyvind; Fossmark, Reidar
Abstract: Background and objectives: Small intestinal neuroendocrine tumors (SI-NETs) are slow growing but have frequently metastasized at the time of diagnosis. Most patients are operated with either curative intent or with intent to prolong overall survival. In the current study we have examined overall and disease-free survival in patients operated for SI-NETs. Methods: All patients with a histological diagnosis of SI-NET at St Olav's hospital in the period 1998–2018 were reviewed retrospectively. Patient, disease and treatment characteristics including European Neuroendocrine Tumor Society (ENETS) TNM staging classification, surgery type, time to recurrence and survival were recorded. Results: A total of 186 patients were identified, whereof 54.3% male, median age at operation 68 years. The majority (n = 141 (75.8%)) underwent elective surgery and surgery was considered curative (radical) in 120 (64.5%) patients. Median estimated overall survival was 9.7 years (95% CI 7.6–11.8) for the entire population. Stage of disease, carcinoid heart disease, age, elective surgery, preoperatively known SI-NET, curative surgery and synchronous cancer were associated with survival in a multivariate analysis. Thirty-six of 120 (30%) patients had disease recurrence after a median follow-up time of 5.5 years, with a median estimated recurrence-free survival of 9.1 (5.4–12.9) years. Recurrence free survival was associated with age and synchronous cancer. Conclusions: Patients with SI-NETs had long overall survival which seemed influenced by stage of disease, presence of carcinoid heart disease, an elective surgery, preoperatively known SI-NET, age and synchronous cancer. Appropriate preoperative diagnostic procedures and elective surgeries seem beneficial and should be aimed for. Highlights: Small intestinal neuroendocrine tumours have often metastasized when diagnosed Overall survival after surgery is long, also in patients with metastatic disease. Advanced stage and carcinoid heart disease is associated with shorter survival. Elective surgery and a known preoperative diagnosis seem favorable.